Struggles for African independent education and land rights on the Rand and the significance of the Tsewu court case, 1903–1905: A new analysis (Historia, 2021)
The years between 1886 and 1910 were among the most dramatic in the history of southern Africa. Scholars have documented Johannesburg's urban history and racial politics during this period. What has often been overlooked, however, and which this article draws attention to in a fresh analysis, is the connection between the colonial state's limitation of African rights to land ownership and the development of the struggle for an independent system of education for Africans. At the local level, this broader struggle was expressed explicitly in African discontent at municipal administrative failure to address the issues of adequate sanitation, land rights, tenure security, and prospects for upward mobility. This article argues that it is in a reassessment of the significance of the 1905 litigation initiated by Reverend Edward Tsewu which provides a basis for this new inquiry into the connection between the African struggle for property rights and independent education.
Keywords: Land ownership; education; independent churches; South Africa; Edward Tsewu